Successful Trials with Chirpine (Pinus roxburghii) in Madhya Pradesh - Dutta, J. J.; Tomar, M. S. (Indian Forester, 1964)
Regular trials with chirpine, an exotic in Madhya Pradesh, were started in 1907 at Supkhar (North Balaghat) at an elevation of 762 meters. The object was to restock large blanks in sal forest and to find out whether chir can be used as nurse for young sal in this frosty locality. Successful plantations of all India Q. I have since been raised and the value of chir as a main crop has recently been realized. Analysis of growth data indicates that the mean annual increment of chir is about 6.65 m3 per hectare as compared to 4.69 and 4.93 m3 in case of Q. I sal and teak respectively. It clearly indicates that the potential productivity of the site is much more than what it is producing under indigenous hardwood stands. A beginning may, therefore, be made in replacing low quality miscellaneous hardwood forests into monocultures of fast growing species leaving valuable teak and sal forest untouched for the present. Tropical conifers will be preferred as they are most suited for industrial use and yield long fibre pulp, so highly priced by pulp indutry.